The Positive Impact of Game-Assisted Project Based Learning Model on Students’ Critical Thinking Ability in Mathematics Learning - Rahmadhani, Della Ayu; Herwin; Nunung Lusiana (Universitas Pendidikan Ganesha, 2024)
Anxiety and difficulty understanding the material in mathematics learning in children results in a decrease in children's critical thinking abilities. The aim of this research was to analyze the application of the pure PjBL model and the game-based PjBL model to children's critical thinking abilities. This research was a type of quantitative research with experimental methods. The research design used was Mathing Pretest Posttest Control Group Design. The population of this research was between grades 1-6. The sample for this research is 32 grade 5 students divided into 2 classes, namely the control class and the experimental class. The method used to collect data was observation and tests. The instrument used to collect data was a question sheet. The data analysis technique was carried out using the t test and anova test using the SPSS 25 application. The results of the analysis were the pure PjBL model and game-based PjBL, both of which saw an increase in scores before and after being given treatment. Comparison between the game-based PjBL model and the pure PjBL model shows that the game-based PjBL model was superior to the pure PjBL. The conclusion of this research was that both pure and game-based PjBL models have an influence on critical thinking skills and the use of the game-based PjBL model was superior in improving critical thinking skills compared to the pure PjBL model.